2021
DOI: 10.1037/bne0000482
|View full text |Cite
|
Sign up to set email alerts
|

Social behavior in prepubertal neurexin 1α deficient rats: A model of neurodevelopmental disorders.

Abstract: Loss-of-function mutations in the synaptic protein neurexin1α (NRXN1α) are associated with several neurodevelopmental disorders, including autism spectrum disorder (ASD), schizophrenia, and attentiondeficit hyperactivity disorder (ADHD), and many of these disorders are defined by core deficits in social cognition. Mouse models of Nrxn1α deficiency are not amenable to studying aspects of social cognition because, in general, mice do not engage in complex social interactions such as social play or prosocial help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…Mice lacking Nrxn1 exhibit deficits in core symptoms related to ASD. Specifically, Nrxn1α mutants display deficits in the social domain including increased social preference, decreased social investigation, decreased social interaction, and increased aggression [ 35 , 46 , 47 , 48 ]. Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ].…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mice lacking Nrxn1 exhibit deficits in core symptoms related to ASD. Specifically, Nrxn1α mutants display deficits in the social domain including increased social preference, decreased social investigation, decreased social interaction, and increased aggression [ 35 , 46 , 47 , 48 ]. Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ].…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%
“…Furthermore, they show stereotypic and repetitive behaviors such as increased grooming, impaired nest-building, altered novelty responsiveness, and habituation [ 31 , 35 , 38 ]. In addition, several behaviors were reported that relate to ASD comorbidities including deficits in learning and cognition, locomotor activity, motor performance, award processing, and anxiety-like behaviors [ 31 , 35 , 36 , 38 , 46 , 47 , 48 , 49 ]. Although the social, stereotyped, and repetitive behaviors are commonly studied, sensory behaviors have received less attention in this model.…”
Section: From Human Asd Genetics To Translational Behavioral Phenotype In Mouse Modelsmentioning
confidence: 99%
See 3 more Smart Citations